(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Education is a cornerstone for societal development, equipping individuals with essential knowledge and skills to improve quality of life and foster national progress. In Nigeria, Social Studies, as a value-oriented discipline, plays a pivotal role in cultivating responsible and active citizens. However, the persistent decline in students’ academic performance in Social Studies, particularly in the Basic Education Certificate Examination (BECE), is a significant concern. This study examines the influence of school routine activities, including co-curricular participation, classroom attendance, and classroom assignments, on students’ academic performance in Social Studies in Cross River State. Grounded in Jean Piaget’s Cognitive Theory of Learning, the research adopted an ex-post facto design, drawing a stratified random sample of 1,037 Junior Secondary School III students across 30 public secondary schools in seven local government areas. Data analysis revealed that co-curricular activities, regular classroom attendance, active classroom participation, and positive peer relationships significantly predicted students’ performance in Social Studies. These findings underscore the importance of holistic educational strategies, emphasizing active engagement, infrastructure development, and the integration of iinteractive learning methods. The study recommends increased government investment in educational facilities, the adoption of activity-based teaching approaches, and strengthened efforts to foster student engagement. By addressing these factors, the study aims to enhance Social Studies outcomes, contributing to the broader goal of national development.